تقييم تأثير ربط أنظمة الخلايا الكهروضوئية على موثوقية أنظمة التوزيع الكهربائيّة المضيفة باستخدام محاكاة مونتِ كارلو المتكيّفة - حجار, عمار; محمود, شعيب; بو سلامه, جورج (Latakia University Journal -Engineering Sciences Series, 2019)
Traditional power systems face many challenges. Such as, the increasing demand for electricity, Potential for fossil fuel depletion, Emissions of greenhouse gases from generation plants. In addition to the difficulty of building new electrical networks technically, economically and environmentally. Therefore, electric power foundations have tended to generate electricity from new and renewable sources of energy because they are free, sustainable and environmentally friendly. The Photovoltaic systems (PVS) are the most important power generators that can be connected to electricity networks. However, the use of photovoltaic systems may affect the reliability of electrical distribution systems due to the intermittent nature of solar radiation. So it is important to study the effect of connecting/disconnecting photovoltaic systems on the reliability of host electrical distribution systems. In order to study the effect of connecting/disconnecting the PVS on the reliability of host electrical distribution systems, the adaptive and non-adaptive Monte Carlo Simulation methods have been applied to the RBTS Bus 2. The statistical results were compared using the MATLAB software environment, where a random model was used to simulate the randomization in the generation from the PV systems. The results of this study showed the efficiency and superiority of the Adaptive Monte Carlo simulation method in evaluating the reliability of the distribution systems hosting the PV systems. Moreover, the PV systems have contributed in improving the reliability of the host network. تواجه أنظمة الطاقة الكهربائية التقليدية العديد من التحديات، مثل زيادة الطلب على الطاقة الكهربائية، احتمال نفاذ الوقود الأحفوري، انبعاث الغازات الملوثة للبيئة من محطات التوليد، بالإضافة إلى صعوبة بناء شبكات كهربائية جديدة من الناحية الفنية والاقتصادية والبيئية. لذا، اتجهت مؤسسات الطاقة الكهربائية نحو توليد الطاقة الكهربائية من مصادر الطاقة الجديدة والمتجددة كونها مجانية، مستدامة، وصديقة للبيئة. تعتبر أنظمة الخلايا الكهروضوئية (Photovoltaic Systems:PVS) من أهم مولدات الطاقة الكهربائية التي يمكن رفد الشبكات الكهربائية بها، لكن قد يؤثر هذا العمل على موثوقية أنظمة التوزيع الكهربائية بسبب الطبيعة المتقطعة للإشعاع الشمسي. لذلك، لا بد من دراسة تأثير ربط/عزل أنظمة الخلايا الكهروضوئية على موثوقية أنظمة التوزيع الكهربائية المضيفة. لدراسة تأثير ربط/عزل أنظمة الخلايا الكهروضوئية (PVS) على موثوقية أنظمة التوزيع الكهربائية المضيفة تم في هذا البحث تطبيق كل من طريقتي محاكاة مونتِ كارلو غير المتكيّفة والمتكيّفة على شبكة توزيع كهربائية اختباريّة RBTS Bus 2، وتم مقارنة النتائج الإحصائية لكل منهما وذلك باستخدام بيئة MATLAB البرمجيّة، حيث تم استخدام نموذج عشوائي لمحاكاة العشوائية في توليد الطاقة الكهربائيّة من أنظمة PV. لقد بيّنت نتائج الدراسة كفاءة وتفوق طريقة محاكاة مونتِ كارلو المتكيّفة في تقييم موثوقية أنظمة التوزيع المُضيفة لأنظمة PV, كما بينت أنّ أنظمة PV تساهم في تحسين موثوقية الشبكة المضيفة.